1981
DOI: 10.1139/x81-067
|View full text |Cite
|
Sign up to set email alerts
|

Container- and nursery-grown black oak seedlings inoculated with Pisolithustinctorius: growth and ectomycorrhizal development following outplanting on an Ozark clear-cut

Abstract: Containerized and bare-rooted black oak (Quercusvelutina Lam.) seedlings were inoculated with vegetative mycelial inoculum of Pisolithustinctorius and were grown in a greenhouse and a southern Missouri nursery, respectively. Following outplanting on a typical Missouri Ozark reforestation site, field data revealed that Pisolithus ectomycorrhizae increased survival and growth of the container-grown seedlings. Container-grown seedlings inoculated with Pisolithus exhibited significantly greater shoot and root grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

1984
1984
2003
2003

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 0 publications
4
13
0
Order By: Relevance
“…Noteworthy studies are related to the selection of those fungi species and isolates which best adapt to the environmental conditions [4,21,29], the most effective inoculum production techniques [6,14,21,22,24,[26][27][28], and the inoculation and production of forestry species in the nursery [1,2,19]. These studies and many others have contributed to a considerable increase in profitability of the forest plant production [6,19] and also the use of mycorrhized plants for afforestations purposes [7,23].…”
Section: Introductionmentioning
confidence: 99%
“…Noteworthy studies are related to the selection of those fungi species and isolates which best adapt to the environmental conditions [4,21,29], the most effective inoculum production techniques [6,14,21,22,24,[26][27][28], and the inoculation and production of forestry species in the nursery [1,2,19]. These studies and many others have contributed to a considerable increase in profitability of the forest plant production [6,19] and also the use of mycorrhized plants for afforestations purposes [7,23].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies on acid coal spoils in Appalachia determined that seedlings inoculated with P. tinctorius in most instances grew better than seedlings that were inoculated with T. terrestris (Berry and Marx 1977, 1978, Marx and~rtman 1979, Berry 1982, Rice et al 1982). Containerized and bare-root seedlings inoculated with P.· tinctorius have also shown good growth performance on borrow pits (Ruehle 1980, Goodwin 1982, prairie soils (Baer and Otta 1981), disturbed road sites (Anderson et al 1983) and routine reforestation sites in southern United States (Marx et al 1977, Mexal 1980, Dixon et al 1981, Kais et al 1981, Ruehle et al 1981), Nicholas and Hutnik (1971) …”
Section: Investigations Ofmentioning
confidence: 99%
“…tinctorius 1n poor soils amended with fertilizer or sewage :ludge, Ruehle et al (1981) found mycorrhizal reatments R.:_ tinctorius and~ terrestris provided no consistent advantage in containerized pine seedlings, while Dixon et al (1981) found no advantage for ·these isolates on bare-root oak seedlings outplanted on reforestation sites, Beckjord and McIntosh (1984) found no growth differences between northern red oak seedlings inoculated with!. :_ tinctorius, f.:_ geophilum and Scleroderma auranteum Pers.…”
Section: Investigations Ofmentioning
confidence: 99%
“…Now, plantings of red (Quercus rubra L.) and black (Q. velutina Lain.) oak are becoming more common for the revegetation of reclaimed lands, cut over sites and old fields (Dixon et al 1981b;Andersen et al 1983;Beckjord and Mclntosh 1984). Planted oak seedlings are characterized by acceptable survival but poor juvenile growth (Russell 1971;Loftis 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports indicate that survival and juvenile growth of oaks planted on adverse sites can be improved if the roots of the seedlings are colonized by the ectomycorrhizal fungus Pisolithus tinctorius (Pers. ) Coker and Couch (Dixon et al 1981b;Anderson et al 1983;Beckjord and McIntosh 1984).…”
Section: Introductionmentioning
confidence: 99%